A Summary Report – PEF Grant ‘Khirbat al-Mafjar Archaeological Project, Jericho’ - Hawari, Mahmoud (2022)
PROJECT ABSTRACTThe Khirbat al-Mafjar Archaeological Project in Jericho (2009–2014) was initiated to achieve a better understanding of Hisham’s Palace within the context of its historical and cultural landscape, and the phenomenon of the Umayyad palaces in the Levant. Six seasons of landscape archaeological survey and excavations in the hinterland of the palace have revealed a large enclosure wall surrounding the palace and an extensive water management system. The elucidation of these findings changes our perception of Hisham’s Palace. It is no longer a free-standing monument, but a palatial complex at the centre of a large agricultural estate aimed at generating revenues and expanding Umayyad political power and administration. This body of fieldwork and research will be published in a book form. The aim of the present project for which the grant will cover, is to complete the previous topographic survey leading to publication.